2007
DOI: 10.1590/s0100-84042007000300018
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in the structure and floristic composition of "restinga" vegetation in southeastern Brazil

Abstract: -(Spatial variation in the structure and floristic composition of "restinga" vegetation in southeastern Brazil). We examined large-scale spatial variation of structural parameters and floristic composition in open Clusia scrub, a vegetation type of the Brazilian "restingas" (sandy coastal plain vegetation). This vegetation is organized in islands separated by sandy stretches with sparse herbaceous vegetation. We located 12 sample areas on three consecutive beach ridges, lying parallel to the coastline and at d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 30 publications
1
41
1
10
Order By: Relevance
“…Phytosociological data for northern Rio de Janeiro (Assumpção & Nascimento 2000; Costa & Dias 2001;Moreno et al 2003;Pessoa & Oliveira 2006;Pimentel et al 2007;Silva & Nascimento 2001) suggest that the region encompasses the so-called tabuleiro forests (coastal lowland forests on Tertiary deposits) in the lowlands and xeromorphic (restinga) vegetation in the coastal areas.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Phytosociological data for northern Rio de Janeiro (Assumpção & Nascimento 2000; Costa & Dias 2001;Moreno et al 2003;Pessoa & Oliveira 2006;Pimentel et al 2007;Silva & Nascimento 2001) suggest that the region encompasses the so-called tabuleiro forests (coastal lowland forests on Tertiary deposits) in the lowlands and xeromorphic (restinga) vegetation in the coastal areas.…”
Section: Study Areamentioning
confidence: 99%
“…To make those associations, we consulted floristic studies undertaken in montane and submontane areas (Kurtz & Araujo 2000;Moreno et al 2003;Pessoa & Oliveira 2006); dense lowland forest and semideciduous forest (Silva & Nascimento 2001;Kurtz et al 2009); restinga (Costa & Dias 2001;Pimentel et al 2007); and herbaceous and hygrophytic coastal vegetation ecosystems (IBGE 1992;Costa & Dias 2001;Bove et al 2003).…”
Section: Relationships Between Fossil Pollen Records and Recent Vegetmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytosociological studies conducted in the region (Assumpção & Nascimento 2000;Silva & Nascimento 2001;Moreno et al 2003;Pimentel et al 2007) identified deciduous forests on top of Tertiary coastal plateaus, and a xerophytic type of vegetation (restinga) near the shore. The restinga vegetation is strongly influenced by the sea, and presents several grades of physiognomy (i.e., from herbaceous to shrubby woodlands).…”
Section: Study Areamentioning
confidence: 99%
“…Depending on the functional diversity variation among coexisting species, a more efficient use of resources is expected, as at the same time decreasing interspecific competition, which overall may increase ecosystem productivity (Scherer-Lorenzen et al, 2007). On the other hand, many tropical vegetation types have few species that attain high dominance at the community level, mainly in terms of biomass, in contrast to many subordinate or rare species (Hubbell, 2001;Macía and Svenning, 2005;Pimentel et al, 2007). Thus, one may expect that the higher abundance of a few species will be the main driver of community structure that modulate the magnitude of fluxes of energy and matter in ecosystems (Grime, 1998;Dangles and Malmqvist, 2004).…”
Section: Floristic Composition and Diversity And Its Relations To C Amentioning
confidence: 99%